Ethical Dimensions of Science: Philosophical Perspectives on the Responsibilities of Scientists - Muhammad Idris; Abdullah Sinring; Anshari Anshari (Journal on Education, 2024)
This study examines the ethical dimensions of science, with the aim of exploring how ethics play a role in scientific research and technological development. This study addresses several important issues, such as ethics in human and animal research, the impact of technology on society, and the social responsibility of scientists. In this context, we review various approaches to ethical philosophy, such as deontology, which emphasizes the moral obligation of scientists to act in accordance with ethical principles, and utilitarianism, which focuses more on outcomes that benefit society at large. Furthermore, this study underscores the significance of ethical oversight mechanisms, like ethics committees (Institutional Review Boards/IRBs), in guaranteeing that research adheres to moral standards and does not cause harm to subjects or society. We also discuss ethical dilemmas that arise in modern research and technology, such as genetic engineering, which raises questions about human genetic editing and potential risks to the ecosystem, and nuclear fusion research, which raises questions about the balance between the benefits of clean energy and potential risks to human and environmental safety. This study emphasizes that scientists, despite their focus on scientific objectivity, have a moral responsibility to consider the social impacts of their discoveries.